Reservoirs and transmission routes of leprosy; A systematic review. - Thomas Ploemacher; William R Faber; Henk Menke; Victor Rutten; Toine Pieters (Public Library of Science (PLoS), 2020)
Leprosy is a chronic infectious disease caused by Mycobacterium leprae (M. leprae) and the more recently discovered Mycobacterium lepromatosis (M. lepromatosis). The two leprosy bacilli cause similar pathologic conditions. They primarily target the skin and the peripheral nervous system. Currently it is considered a Neglected Tropical Disease, being endemic in specific locations within countries of the Americas, Asia, and Africa, while in Europe it is only rarely reported. The reason for a spatial inequality in the prevalence of leprosy in so-called endemic pockets within a country is still largely unexplained. A systematic review was conducted targeting leprosy transmission research data, using PubMed and Scopus as sources. Publications between January 1, 1945 and July 1, 2019 were included. The transmission pathways of M. leprae are not fully understood. Solid evidence exists of an increased risk for individuals living in close contact with leprosy patients, most likely through infectious aerosols, created by coughing and sneezing, but possibly also through direct contact. However, this systematic review underscores that human-to-human transmission is not the only way leprosy can be acquired. The transmission of this disease is probably much more complicated than was thought before. In the Americas, the nine-banded armadillo (Dasypus novemcinctus) has been established as another natural host and reservoir of M. leprae. Anthroponotic and zoonotic transmission have both been proposed as modes of contracting the disease, based on data showing identical M. leprae strains shared between humans and armadillos. More recently, in red squirrels (Sciurus vulgaris) with leprosy-like lesions in the British Isles M. leprae and M. lepromatosis DNA was detected. This finding was unexpected, because leprosy is considered a disease of humans (with the exception of the armadillo), and because it was thought that leprosy (and M. leprae) had disappeared from the United Kingdom. Furthermore, animals can be affected by other leprosy-like diseases, caused by pathogens phylogenetically closely related to M. leprae. These mycobacteria have been proposed to be grouped as a M. leprae-complex. We argue that insights from the transmission and reservoirs of members of the M. leprae-complex might be relevant for leprosy research. A better understanding of possible animal or environmental reservoirs is needed, because transmission from such reservoirs may partly explain the steady global incidence of leprosy despite effective and widespread multidrug therapy. A reduction in transmission cannot be expected to be accomplished by actions or interventions from the human healthcare domain alone, as the mechanisms involved are complex. Therefore, to increase our understanding of the intricate picture of leprosy transmission, we propose a One Health transdisciplinary research approach.